Оценка жизнеспособности геноплазмы плодовых культур после криосохранения в парах жидкого азота при –183-185ºС - Вержук, В.Г.; Павлова, А.В.; Тихонова, О.А.; Борзых, Н.В.; Дорохов, Д.С. (Фактори експериментальної еволюції організмів, 2013)
Aims: to study the ability storage of vegetative shoots and buds of fruit crops to withstand ultra-low temperature of the vapor-liquid nitrogen. Methods: cuttings dried up to the humidity of 28–35 %, frozen gradually to –49ºС and placed in storage in pairs liquid nitrogen at –183–185ºС. As a cryoprotectors used different concentration of glycerin and sucrose. The chemical composition of fruits determined by the protocols: [10]. Results: Cuttings currant, planted in the field, showed good viability: 60–90%. The viability of processed cryoprotectors buds was 69,6–72 %. The biochemical composition of fruits: the differences between the control and experience were insignificant. Conclusions: Results of the research showed that the cuttings and buds fruit crops after storage in liquid nitrogen remain viable at the level of 60–90 %.